Structure-Based Technique for Object Detecting in UAV Imagery - David G. Asatryan (Изд-во НАН РА)
In this paper, the problem of automated detection of anomalies in the video, filmed in the controlled area on board of the UAV is considered. The complexity of the problem associated with the effect of multiple factors on the quality of the image is pointed out. Expediency of processing methods using the structural properties of the image, stable with respect to a number of noise and distortion is justified. We propose two approaches to use the structural properties of an image.
Keywords: Mathematics; Analysis